Prescription Analysis To Evaluate Rational Use Of Antimicrobials - HANMANT AMANE,; PRIYADARSHINI KOP., (International Journal of Pharma and Bio Sciences, 2011)
One of the most important problems encountered by healthcare system is the increasing prevalence of antimicrobial resistance. It may result from irrational or inappropriate use of antibiotics. The present study was undertaken to screen rational use of antimicrobials in outpatient department (OPD). Prescriptions from medicine, surgery, obstetrics and gynecology (OBG) and pediatrics OPDs were collected over a period of two months. Prescriptions containing antimicrobial drugs were analyzed for appropriateness in dosage, duration of therapy, and fixed dose drug combinations (FDCs). The maximum number of antimicrobial FDC prescriptions (52.17%) was found in surgery OPD as compared to other three departments, of which 75% FDC prescriptions were irrational, whereas in OBG OPD all four FDC prescriptions were irrational. Out of total FDCs from all the departments, 62.79% FDCs were irrational. It is the need of the time doctors should be made aware of the demerits of irrational prescribing and they should detain from prescribing irrational FDCs.